Pengembangan Model Modifikasi Kurikulum Sekolah Inklusif Berbasis Kebutuhan Individu Peserta Didik - Abdul Salim (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2010)
The aims of this research are to develop the model of modified curriculum for inclusive schools based on the individual needs and to know the empirical validity of the curriculum modified. The data is collected through interview, observation and documentation. The data is analysed by using descriptive technique. The result of this research show that: 1) The understanding of teachers and Headmaster Prinsipal in inclusive schools about the content of curriculum modified guidance book, such as: (a) 46% well understanding, (b) 32,65% good understanding, (c) 16,32% bad understanding (d) 4% worst understanding. 2).The empiric validities of guidance books of curriculum modification shows: (a) 88.2% teachers and head master have agreed the content of guidance books’ substance the meaning/the substance of guidance books, only 11.8% who are disagree. (b) The readability of guidance books: 88.2% guidance books have used proper language in its writing and only 11.8% which haven’t used proper language yet. (c) 88.2% guidance books have used good and proper style of writing while out of 11,8% haven’t answered the question. And (d) the appearance of guidance books: 64.7% respondents states that guidance books have had good appearance, 29.2% consider that the appearance hasn’t been good enough yet and the rest, 11.8% do not answer the question. ABSTRAK Penelitian ini bertujuan untuk mengembangkan model modifikasi kurikulum anak berkebutuhan khusus dan mengetahui validitas empiris modifikasi kurikulum. Pengumpulan data dilakukan melalui interview, observasi dan dokumentasi. Tehnik analisis data menggunakan deskriptif kualitatif. Hasil penelitian menunjukkan bahwa 1) Pemahaman guru dan kepala sekolah terhadap panduan modifikasi kurikulum menunjukkan :(a) sangat baik 46,93%, (b) baik 32,65%, (c) kurang baik 16,32%, dan 4% tidak baik. 2) Validitas empiris buku panduan menunjukkan bahwa: a). 88,2% guru dan kepala sekolah menyetujui kebermaknaan/Substansi buku panduan dan 11% kurang menyetujui. b). 88,2% menyatakan buku panduan telah menggunakan bahasa yang baik dan sisanya 11,8% menyatakan belum. c) 88,2% menyatakan buku panduan telah menggunakan gaya penulisan yang singkat, padat dan baik, sedangkan sisanya 11,8% tidak menjawab pertanyaan. c). 64,7% menyatakan penampilan buku panduan telah memiliki penampilan yang baik, 29,4% belum baik dan 11,8% tidak menjawab pertanyaan.